Effect of composition of commercial whey protein preparations upon gelation at various pH values - Ramos, Óscar L.; Pereira, Joana O.; Silva, Sara I.; Amorim, Maria M.; Fernandes, João C.; Lopes-da-Silva, José A.; Pintado, Manuela E.; Malcata, F. Xavier (Food research international, 2012)
The major goal of this research effort was to comprehensively characterize various whey protein products available in the market — including one whey protein isolate (WPI) and three whey protein concentrates (two forms of WPC 80, and WPC 50), with regard to the effects of specific components (e.g. lecithin and minerals) and concentration of β-lactoglobulin (β-Lg) and α-lactalbumin upon thermal and gelation properties at various pH values (using micro differential scanning calorimetry, μDSC, and oscillatory rheometry). At pH values far from the isoelectric point of whey proteins, denaturation and aggregation appeared as one single endothermic peak in the corresponding μDSC heating thermograms, for WPI and both WPC 80; however, they appeared as separate transitions at pH 5. Acidic conditions increased the temperature of occurrence of the dominant endothermic transition associated to β-Lg, thus increasing the thermal stability of WPI, WPC 80A and WPC 80B. Gelation took place at the lowest temperature when pH was set at 5. WPI, WPC 80A and WPC 80B exhibited the highest G′ values at pH 5 — whereas WPI led to stronger gels than WPC, irrespective of pH. In the case of WPC 50, gelation did not occur at all. ► Whey protein (WP) products were characterized and their composition was assessed. ► Their endothermic and exothermic processes were found as separate transitions at pH 5. ► Decreasing pH increases stability of WP products. ► Strength of WPI gels was higher than WPCs ones, irrespective of pH. ► Soy lecithin did not affect thermal gelation properties of WP products.